Babel' in Context A Study in Cultural Identity - Sicher, Efraim (Borderlines: Russian and East European-Jewish Studies, 2012)
Isaak Babel (1894-1940) is arguably one of the greatest modern short story writers of the early twentieth century. Yet his life and work are shrouded in the mystery of who Babel was-an Odessa Jew who wrote in Russian, who came from one of the most vibrant centers of east European Jewish culture and all his life loved Yiddish and the stories of Sholom Aleichem.This is the first book in English to study the intertextuality of Babel's work. It looks at Babel's cultural identity as a case study in the contradictions and tensions of literary influence, personal loyalties, and ideological constraint. The complex and often ambivalent relations between the two cultures inevitably raise controversial issues that touch on the reception of Babel and other Jewish intellectuals in Russian literature, as well as the "Jewishness" of their work.